Promoting and supporting breastfeeding in a protracted emergency setting-Caregivers' and health workers' perceptions from North-East Nigeria - Amat Camacho, Nieves; Chara, Abdullahi; Briskin, Emily; Pellecchia, Umberto; Kyi, Htet Aung; de Rubeis, Maria Livia; Hussain, Faisal; Ahmed, Tasneem; Ogundipe, Oluwakemi F; Burzio, Chiara; Kamis, Uba; Bukar, Lawan M; et al. (My University, 2023)
Breastfeeding (BF) should be protected, promoted, and supported for all infants in humanitarian settings. The re-establishment of exclusive BF is also a central part of the management of acutely malnourished infants under 6 months (<6 m). Médecins Sans Frontières (MSF) runs a nutrition project in Maiduguri, a protracted emergency setting in North-East Nigeria. This study aimed to explore caregivers' (CGs) and health workers' (HWs) perceptions of BF practice, promotion, and support among CGs with infants <6 m in this setting.
Keywords: breastfeeding; breastfeeding support; humanitarian settings; infant malnutrition; North-East Nigeria